1987
DOI: 10.1161/01.res.60.4.560
|View full text |Cite
|
Sign up to set email alerts
|

Use-dependence of ryanodine effects on postrest contraction in ferret cardiac muscle.

Abstract: During an investigation of the effect of ryanodine on contractions in cardiac muscle, it was found that long rest periods removed all or most of the drug's effect. Therefore, we studied the kinetics of block development and recovery from block produced by low concentrations of ryanodine (1-100 pM) on the postrest contractions of ferret papillary muscle. At 100 pM, ryanodine depressed steady-state contraction amplitude slightly (4.2 ± 1.1% mean ± SEM, n = 10) but strongly inhibited (40-80%) the first contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In human myocardium, several authors reported a reduced Ca 2ϩ -uptake capacity of the sarcoplasmic reticulum in failing dilated cardiomyopathy (13,21,40) To evaluate whether a functional SR is a prerequisite for post-rest potentiation in human myocardium, the influence of ryanodine on post-rest contractions was investigated. Ryanodine was shown to deplete SR Ca 2ϩ stores (48) and has been found to abolish post-rest potentiation of contractile force in ferret (49), canine (50) and rat (5, 51) myocardium. This effect was attributed to a ryanodine-induced increased leak of Ca 2ϩ from the SR by blocking the release channel in a subconducting open state (52).…”
Section: Discussionmentioning
confidence: 99%
“…In human myocardium, several authors reported a reduced Ca 2ϩ -uptake capacity of the sarcoplasmic reticulum in failing dilated cardiomyopathy (13,21,40) To evaluate whether a functional SR is a prerequisite for post-rest potentiation in human myocardium, the influence of ryanodine on post-rest contractions was investigated. Ryanodine was shown to deplete SR Ca 2ϩ stores (48) and has been found to abolish post-rest potentiation of contractile force in ferret (49), canine (50) and rat (5, 51) myocardium. This effect was attributed to a ryanodine-induced increased leak of Ca 2ϩ from the SR by blocking the release channel in a subconducting open state (52).…”
Section: Discussionmentioning
confidence: 99%
“…Currently accumulating evidence suggests that the resumption of electrical stimulation following a brief stop yields contractions highly sensitive to releasable Ca 2+ from SR [1,6,29]. In the rat ventricular muscle, PRC is recognized as a composite function of timeand beat-dependent recycling of Ca 2+ within the SR [33] combined with a small net cellular Ca 2+ gain through the Na + /Ca 2+ exchange process [38].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, we are the first analyzing the recovery process of PRC, to address the underlying mechanisms associated with the development of abnormal mechanics in diabetes. SR Ca 2+ release contributes largely to the mechanism of postrest potentiation [1,6,29]. Malecot et al [28] have reported that the first component of PRC may be caused by SR Ca 2+ release and the second one by increased Ca 2+ influx during the action potential via the L-type Ca 2+ channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] This alteration of [Ca 2+ ] i transient may be involved in changes of action potential configuration after a rest period. In fact, Bers demonstrated that the APD of rabbit papillary muscle shortened after a rest period which was accompanied by a greater and faster developed tension.…”
Section: Discussionmentioning
confidence: 99%